Ecological rehabilitation of post-bauxite mine spoil using a multi-strata agroforestry model with specialized soil amendments in Tan Rai, Vietnam - Hoang Huyen Thi, Ngoc; Nguyen Manh, Ha; Nguyen Cong, Long; Luu The, Trung; Nguyen Thi Huyen, Trang; Nguyen Thi, Thuy; Nguyen Thai, Son; Nguyen Thanh, Men; Nguyen Duc, Toan (Vietnam Journal of Earth Sciences, 2025)
In the face of accelerating land degradation from open-pit mining, ecological rehabilitation has become a cornerstone strategy for restoring ecosystem functions and sustainability. This study evaluated the early outcomes of a pilot multi-strata agroforestry model designed for post-bauxite mine spoil at the Tan Rai site, Vietnam. The system combined Pinus caribaea Morelet, Bixa orellana L., and Sphagneticola trilobata (L.) Pruski, integrated with soil amendment products such as controlled-release NPK fertilizers, superabsorbent polymers, and polyacrylamide. Over a six-year observation period, comprising two years of active management followed by four years of natural succession, plant growth performance, nine soil physicochemical properties, and eight heavy metal concentrations were assessed through six sampling campaigns. Results indicated significant improvements in vegetation structure and soil quality. P. caribaea showed strong height growth, while B. orellana exhibited rapid diameter expansion and reached reproductive maturity by year six. Vegetation cover stabilized above 75% after 12 months, accompanied by increasing species diversity. Within the first 24 months, soil organic carbon, available nutrients, cation exchange capacity, and pH improved markedly, while heavy metal levels remained within the safe thresholds specified by QCVN 03:2023/BTNMT. These findings highlight the potential of multi-strata agroforestry, when combined with targeted soil amendments, to accelerate ecological recovery on post-bauxite mine spoils. However, continued monitoring is required to ensure long-term sustainability.